2023
DOI: 10.3390/medicina59030421
|View full text |Cite
|
Sign up to set email alerts
|

Mininvasive Cytoreduction Surgery plus HIPEC for Epithelial Ovarian Cancer: A Systematic Review

Abstract: Background and objectives: The Gold-Standard treatment for Advanced Epithelial Ovarian Cancer remains cytoreductive surgery followed by systemic chemotherapy. Surgery can be performed either by an open or minimally invasive approach (MIS), although the former remains the most widely used approach. Recently, Van Driel et al. proved that adding 100 mg/m2 of Cisplatin in Hyperthermic Intraperitoneal Chemotherapy (HIPEC) at Interval Debulking Surgery (IDS) gives a disease-free survival (DFS) advantage. Similarly, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…CD4+ cells play an important role in the immune system, mainly expressed by helper T cells, and they are receptors for TCR recognition of antigens. Abnormal levels of T lymphocytes can lead to a decrease in physiological functions in the body[ 25 , 26 ]. The study concluded that the CD3+ and CD4+ markers in the postoperative research group were higher compared to the reference group, indicating that minimally invasive laparoscopic surgery under general anesthesia for early ovarian cancer has minimal impact on the immune function of patients.…”
Section: Discussionmentioning
confidence: 99%
“…CD4+ cells play an important role in the immune system, mainly expressed by helper T cells, and they are receptors for TCR recognition of antigens. Abnormal levels of T lymphocytes can lead to a decrease in physiological functions in the body[ 25 , 26 ]. The study concluded that the CD3+ and CD4+ markers in the postoperative research group were higher compared to the reference group, indicating that minimally invasive laparoscopic surgery under general anesthesia for early ovarian cancer has minimal impact on the immune function of patients.…”
Section: Discussionmentioning
confidence: 99%